(595) تطبيق أسلوب تحليل التكلفة والعائد في مجالات إعداد الموازنة العامة Applying cost-benefit analysis in the areas of general budget preparation - عصام الدين زايد (معهد التخطيط القومى, 2026)
يستعرض هذا البحث، الصادر عن معهد التخطيط القومي عام 1965، مفهوم وقياس إنتاجية العمل في الصناعة الاشتراكية، مع التركيز على دورها المحوري في التنمية الاجتماعية والاقتصادية. يوضح المحتوى أن الإنتاجية لا تقتصر فقط على حجم المخرجات لكل عامل، بل تعكس كفاءة المجتمع في استخدام موارده الوطنية، حيث تؤثر عوامل متعددة على نموها، أبرزها الظروف السوسيو-اقتصادية التي تشكل موقف العامل تجاه عمله، بالإضافة إلى التقدم العلمي والتكنولوجي، والتنظيم الإداري لعملية الإنتاج.كما يتناول البحث الجوانب التطبيقية لقياس الإنتاجية من خلال معادلات رياضية ومؤشرات إحصائية، مفضلاً استخدام الوحدات الطبيعية أو الفيزيائية لتقدير مستويات النمو بدقة. ويفصل الملف طرقاً عملية مثل "طريقة تجميع الوقت" (Time-summing method) لربط ساعات العمل الفعلية بالإنتاج، مما يتيح للإدارة تحليل العوامل التي تعيق أو تعزز الإنتاجية، وتحديد الوفورات المحققة في وقت العمل نتيجة لإدخال تقنيات حديثة أو تحسين مهارات القوى العاملة. This research, published by the National Planning Institute in 1965, examines the concept and measurement of labor productivity in socialist industry, emphasizing its pivotal role in socio-economic development. The content clarifies that productivity is not merely a measure of output per worker, but rather reflects society's efficiency in utilizing its national resources. Multiple factors influence its growth, most notably the socio-economic conditions that shape workers' attitudes toward their work, as well as scientific and technological advancements and the administrative organization of the production process. The research also addresses the practical aspects of productivity measurement through mathematical equations and statistical indicators, favoring the use of natural or physical units to accurately estimate growth levels. Furthermore, the document details practical methods, such as the "time-summing method," for linking actual working hours to output. This allows management to analyze factors that hinder or enhance productivity and to identify time savings achieved through the introduction of modern technologies or the improvement of workforce skills.